Ultrasonography Vs. Per Rectal Examination for Uterine Involution in Methyl Ergometrine and Other Supplements Treated Crossbred Cows - Madhwal, Deepa; Sharma, Mridula; Patra, Manas K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Normally calved 36 post-partum HF crossbred cows from first to seventh parity were selected from University Farm and divided randomlyinto 6 equal groups. In all treatment groups (T1 to T5), injections of methyl ergometrine maleate (Ergovet, 2 mg, i/m, OD) at 1/2 hr,2nd and 3rd day post-partum were given. Additionally, in T2, calcium (Mifex, 50 mg/ml, @ 300 ml, i/v) and phosphorus (Tonophosphan,0.2 gm/ml, @ 10 ml, i/m, OD) were injected on second day of calving; in T3, Vit. ADE (Intavita, @ 10 ml, i/m, OD) on the second day ofcalving; in T4, Ceftiofur sodium (Xyrofur, 1 gm, i/m, OD) for three days from the second day of calving, and in T5, Calcium, phosphorus,Vit. A D E and Ceftiofur sodium were given with same dosage. The sixth group (T6, control) was left untreated. Cervical and uterine(previously gravid; PG and non-gravid; NG horns) diameters and uterine involution were examined by USG and per rectal palpation, at5 days interval from day 12 to day 40 post-partum, to observe the effect of methyl ergometrine with and without above combinationson uterine involution. The reduction was observed earlier in T1, T2, and T5, by per rectal palpation compared to USG examination,while in T3, T4 and C, both methods were at the same time. PG and NG horn diameters were reduced significantly (p
Keywords: Methyl ergometrine; Uterine involution; Nutrient supplements; USG; Fertility; Lochial discharge; Pelvic brim